Teamwork Effectiveness in Student’s Final Year Project - Norazah Yusof (International Journal of Emerging Technologies in Learning (iJET), 2021)
The goal of this paper is to deliberate issues pertaining to teamwork effectiveness among students in a university environment. Final year project is an important assessment to measure students’ teamwork skills in the university. Three main factors have been identified that contribute to teamwork effectiveness. The factors are namely interpersonal skills, interdependence and commitment to success. Interpersonal factors include social sensitivity and emotional engagement attributes. In this perspective, measures such as teamwork support, care, trust, honesty and respect towards team members are important key criteria. On the other hand, interdependence among others includes traits such as promoting each other to achieve common goals, bringing the best of each other and helping each other completing the task. Commitment to team success involves high obligation, high motivation, strong common goals and strong shared values and beliefs. In this paper, construct items for each factor are developed based on previous studies. The findings show that these factors are relevant toward the success of the student’s final year project. Lacking these skills may result in poor performance among team members and may lead to unfavorable outcome.